2017
DOI: 10.4236/ojg.2017.73028
|View full text |Cite
|
Sign up to set email alerts
|

Model Design for AMT Data Inversion

Abstract: By analyzing the characters of the mainstream commercial magnetotelluric inversion softwares in dealing with audio magnetotelluric data, a dynamic model-making method for inversion has been developed based on the observed AMT data. This method focusing on model domain can adjust mesh's scale and model's dimension depending on the field data just with a few parameters. By this, it is convenient to study the geo-electrical anomalies variations of different scale or dimensional models. Applying such model-making … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…In this study, we also found an increase in dinocyst, indicating the presence of a marine environment. Moreover, according to [24] and [25], the appearance of keeled forms indicates a relatively deep environment. All these data suggest a depositional environment of medium to outer platform type.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we also found an increase in dinocyst, indicating the presence of a marine environment. Moreover, according to [24] and [25], the appearance of keeled forms indicates a relatively deep environment. All these data suggest a depositional environment of medium to outer platform type.…”
Section: Discussionmentioning
confidence: 99%